Tłumacze bez Granic a status tłumacza - Masłowska, Patrycja (Investigationes Linguisticae, 2019)
The objective of the present article is to analyse the influence of the organisation Translators Without Borders on the status of its volunteers: translators and community interpreters. The first chapter concerns main aspects of the translator's status. The second one presents briefly the types of Translators Without Borders activities, while the next one focuses on the characteristics of the types of translator's and interpreter's work for the organization. The last chapter includes the analysis of the translator's and interpreter's status aspects that are susceptible to impact of the described organization’s activities. Conclusions are ambiguous as the main reason of the Translators Without Borders foundation was not to improve the translator's status. However, membership may be beneficial under certain conditions.